2017
DOI: 10.18632/oncotarget.14487
|View full text |Cite
|
Sign up to set email alerts
|

L1 increases adhesion-mediated proliferation and chemoresistance of retinoblastoma

Abstract: Retinoblastoma is the most common intraocular cancer in children, affecting 1/20,000 live births. Currently, children with retinoblastoma were treated with chemotherapy using drugs such as carboplatin, vincristine, and etoposide. Unfortunately, if conventional treatment fails, the affected eyes should be removed to prevent extension into adjacent tissues and metastasis. This study is to investigate the roles of L1 in adhesion-mediated proliferation and chemoresistance of retinoblastoma. L1 was differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 53 publications
5
34
0
Order By: Relevance
“…Further along this line, a combination of anti-L1CAM antibody and cisplatin was found to improve the therapeutic response in cholangiocarcinoma by enhancing tumor growth inhibition compared to treatment with the drug alone ( 27 ). Recently, Jo et al showed that L1CAM increased the adhesion-mediated proliferation and resistance of Y-79 and SNUOT-Rb1 RB cells to carboplatin, vincristine and etoposide ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further along this line, a combination of anti-L1CAM antibody and cisplatin was found to improve the therapeutic response in cholangiocarcinoma by enhancing tumor growth inhibition compared to treatment with the drug alone ( 27 ). Recently, Jo et al showed that L1CAM increased the adhesion-mediated proliferation and resistance of Y-79 and SNUOT-Rb1 RB cells to carboplatin, vincristine and etoposide ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beginning at 2 weeks after injection, eyeballs were examined daily to monitor tumor formation. A visual grading system was employed to grade the degree of tumor formation from 0–5: grade 0 (no tumor formation), grade 1 (streak-like tumor), grade 2 (plaque-like tumor), grade 3 (definite mass formation), grade 4 (vitreous-filling tumor), and grade 5 (accompanying globe enlargement or eyeball rupture), according to the standard photographs in a previous publication 18 . Two independent observers (D.H. Jo and C.S.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy resistance to antineoplastic agents, including carboplatin, etoposide and vincristine, is a major problem in the treatment of high-risk advanced RB [5,8,9]. Etoposide is well known for its use in the treatment of many malignancies, such as Hodgkin's disease, lung cancer, ovarian cancer, myeloma, gastric cancer and breast cancer [10][11][12][13]; the drug is a DNA topoisomerase-II inhibitor that can directly bind to DNA and cause DNA damage [14].…”
Section: Introductionmentioning
confidence: 99%